Vage Normen sebagai Sumber Hukum Diskresi yang Belum Diterapkan oleh Polisi Penyidik Anak - Abintoro Prakoso (Fakultas Hukum Universitas Islam Indonesia, 2010)
The research is focused on the implementation of vage normen as a discretion law source done by children police penyidik and on the kind of crimes done by children that can be discrete. The method used is the normative legal research through literature that is a research for secondary data as law material. The result proves that the police discreet taken from vage normen is not implemented yet as there is no clear rules about it. the kind of children crimes that may be discreet are clash, stealing, money game, vandalism, dangerous burning for others’ property, stealing, smuggling, crime trial, passing on stolen’s goods, destruction, public means destruction, destroying things, rascals, breaking traffic regulation, dangerous fireworks, being truant, running away from home, psychotropic involve, traffic accident’s suspect, hanging out over midnight, breaking personal rules and smoking.Key words : Vage normen, discretion, investigation, non juridic, well-being of the juvenile